Trabeculae in Patagonian mountain cypress (Austrocedrus chilensis) associated with Phytophthora austrocedri infection - Troncoso, Oscar Alberto (2018)
Phytophthora austrocedri is a straminipilous (heterokonta) organism that causesmortality of Austrocedrus chilensis, an endemic Cupressaceae from the PatagonianAndes forest in temperate South America. This soil pathogen colonizes andkills the roots and extends up to the stem causing necrosis of cambium, phloemand xylem ray parenchyma. An anatomical study of affected tissues was conductedin order to better understand the process of pathogen colonization andtree response. It was found that tracheids of the xylem of affected trees showedlarge numbers of trabeculae, both rod- and plate-shaped. The occurrence ofthese structures was clearly associated with the necrotic lesion area, since thetrabeculae were rare in healthy tissues above the necrotic lesion. Trabeculaeoccurred in a variety of arrangements: solitary or in long files, single, doubleor triple. Our results could indicate that trabeculae proliferation in tracheidsof A. chilensis trees is induced by the stress generated by the P. austrocedriinvasion. Whether this is triggered by a nonspecific stress response or in directresponse to the pathogen remains to be tested.